Thermal Cycle Durability of Heat-Shielding Coatings on the Basis of Zr-Y-O/Si-Al-N under Ion Treatment of Copper Substrates; Advanced Materials Research : Advanced materials, synthesis, development and application; Vol. 880 : Prospects of Fundamental Sciences Development (PFSD-2013) - Sergeev V. P. Viktor Petrovich; Panin V. E.; Rizakhanov R. N.; Koroteev A. S.; Fedorischeva M. V.; Neufeld V. V.; Kalashnikov M. P. (Diagnostics and Engineering of Novel Materials, 2014)
Title screen